Fostering integrated design in an academic environment: process and a method - Aye, Lu; McNiven, Brendon; Holzer, Dominik (Journal of Architecture and Urbanism, 2022)
In conventional building design projects architects make pre-design and conceptual design decisions on buildings and hand these down to structural and building services engineers to follow up with design development. It is well known that the conceptual design stage of a project is the point where decisions make the most impact, and changes can be made at least cost. The sustainability and innovation aspects of projects often suffer in this respect. One way of addressing this is through Integrated Design Methods that set out mobilise the full potential of all design disciplines on a project by getting them to work effectively together. This method involves architect, engineers, contractors, and owners/clients in all design phases. The current literature reported fundamental principles and processes of Integrated Design however current industry practices do not fully embrace them. Introducing integrated design studios into university pedagogies is a key step in addressing this. Reports on methods of setting up integrated design studios in a university context are however rare. The aim of this article is to develop and document the underlying settings for such design studios. The principles and best practices for applying integrated design are identified. A specific framework of settings in university context is developed and the justifications presented. This article may be of value for the industry and universities to setup integrated design studios to better foster integrated design education.